1994
DOI: 10.1080/07421222.1994.11518018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information Technology in Organization Design

Abstract: This paper introduces a set of information technology variables which can be used in designing organizations, We first look at traditional design variables and then present a series of options enabled by modern information technology. We use these IT design variables to describe four prototypical organizationsn which are beginning to appear in the workplace: virtual, negotiated, traditional and vertically integrated. It is argued that an organization designer must also consider how structure and technology inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…For instance, in the organizational context, studies have found that bureaucratic structure restricts the adoption of technology (Hall & Khan, 2002) and ERP implementation (Morton & Hu, 2008). Baroudi and Lucas (1994) argue that bureaucracy creates bottlenecks, and technology can help remove it (Baroudi & Lucas, 1994). Similarly, studies have acknowledged the role of centralized organizational structure on knowledge management (Chen & Huang, 2007).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…For instance, in the organizational context, studies have found that bureaucratic structure restricts the adoption of technology (Hall & Khan, 2002) and ERP implementation (Morton & Hu, 2008). Baroudi and Lucas (1994) argue that bureaucracy creates bottlenecks, and technology can help remove it (Baroudi & Lucas, 1994). Similarly, studies have acknowledged the role of centralized organizational structure on knowledge management (Chen & Huang, 2007).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Although we do not provide a literature review, we should note the bases of knowledge for our analysis and suggestions. Our analysis is informed by our reading of literatures on administrative burden (for a review of this literature, see Chittenden, Kauser, and Poutziouris ), red tape (Bozeman ; Bozeman and Feeney ), behavioral public administration (for a review of this literature, see Battaglio et al 2019), and electronic communications and management (Baroudi and Lucas ; Kyriakou and Loukis ). In one respect, these literatures have a common base—they are increasingly focused on the psychological and cognitive bases of behavior.…”
Section: “Robotic Bureaucracy”: Cause or Solution For Administrative mentioning
confidence: 99%
“…Provide support decision making process by using the stored data. ICT is becoming an essential part of the organizations with the increase investment on it (Baroudi & Lucas, 1994) as well as for individual behaviour. So, it could be stated that ICT has direct effect on organizational behaviour especially on organizational design, intelligence and decision making.…”
Section: Organization Changes In the Ict Development Eramentioning
confidence: 99%